Rugby in global perspective playing on the periphery - Harris, John 1972-; Wise, Nicholas (Routledge focus on sport, culture and society, 2020)
This book critically examines how rugby union has developed in recent years, in nations on the periphery of the sport. Focusing on people and places on the fringes, it examines contemporary issues and challenges within the global game. Such a collection is timely, as the sport's governing body seeks to expand influence and participation beyond the eight core nations, with the 2019 Rugby World Cup in Japan being the first time that that tournament has taken place outside of the core. Presenting case studies from Europe, Africa, North and South America, Asia and the Middle East, this collection offers an interdisciplinary account of a sport that is undergoing a period of significant change. Through examination of topics such as the development of rugby sevens and the growth of women's rugby, it considers what the future may hold for the sport. Rugby in Global Perspective is important reading for students of sport in society, the globalisation of sport, sports studies, sport development and associated fields. It is also a valuable resource for academic researchers working in rugby union or sport in the peripheral rugby nations, as well as those with an interest in cultural geography, sociology, development studies, events studies, event management and sport management